Smartphone Placebo for Nomophobia: A Quasi-Experimental Study on Smartphone Dependency and Toxicity. - Ali, Anuar; Najmi Nuji, Mohd Nur; Omar, Nurul Hanani; Azman Ong, Mohd Hanafi (Pertanika Journal of Social Sciences & Humanities, 2026)
Nomophobia, or the fear of being away from a smartphone, has evolved as a growing concern among university students, often linked to smartphone dependency and toxicity. These conditions are associated with anxiety and declined academic performance. This study introduces a novel intervention, the smartphone placebo, as a naturalistic intervention to manage smartphone dependency without requiring complete digital detoxification. Using a quasi-experimental mixed design, 200 undergraduate students were assigned to experimental (n=100) and control (n=100) groups. The intervention involved the use of a smartphone placebo resembling a smartphone in size and function as a smartphone placebo. Data were collected in three phases: baseline time, follow-up time and evaluation time using a structured questionnaire measuring two dimensions: smartphone dependency and smartphone toxicity. Findings from a mixed-design ANOVA revealed a significant reduction in smartphone dependency and digital toxicity over time in the experimental group compared to the control group. The results indicate that a non-digital-based intervention like a smartphone placebo may help regulate digital attachment behaviours and mitigate toxic usage patterns. This study offers practical implications for digital well-being programs in higher education, suggesting the use of symbolic substitutes to manage nomophobia and improve smartphone dependency. The findings contribute to the growing field of digital behaviour intervention by providing evidence for low-cost, non-technological alternatives to digital detox strategies. The study implies that higher education institutions may adopt this intervention of using smartphones to promote digital literacy. Future research should consider exploring the importance of smartphone placebo in different demographic and educational contexts.